Changes in Food Chains in the Context of Globalization - Belo Moreira, Manuel (The International Journal of Sociology of Agriculture and Food, 2011)
This article highlighting the political and ideological conditions necessary for globalization and the role of the technologies associated with this process is an attempt to explain the nature and dynamics of change in food chains. In this text, a political-economic perspective is employed, relying on well-known theoretical and empirical examples that abound in the literature about globalization of food, and on the underlying theoretical explanation of the structural changes brought about or intensified by the globalization process.It seeks to understand the logic and dynamic that explains why the corporate retailers became the main economic motors of deep and rapid changes in food chains and after a short appraisal of the effects of the changes it seeks to identify the winners and losers of the process.